Bridging Cultures Through Brands: Exploring the Role of Cultural Authenticity and Identity Alignment in Shaping Revisit Intention - Prawira, Nanang Ganda; Jeon, Jeong Ok; Prawira, Mega Fitriani Adiwarna; Prawira, Aura Bulan Andhara; Prawira, Mentari Putrirahayu (Integrasi Sains Media, 2024)
In the era of globalized tourism, destinations function not only as geographic spaces but as communicative platforms for cultural exchange. This study examines how place branding elements—brand image, cultural authenticity, and community engagement—influence revisit intention through the mediating roles of perceived cultural exchange and destination identity alignment. Drawing on theories of intercultural communication and symbolic interactionism, a structural equation modelling approach using PLS-SEM was applied to data collected from 235 tourists visiting culturally significant destinations in Indonesia. The results reveal that perceived cultural exchange is the strongest predictor of revisit intention, while cultural authenticity and brand image significantly shape identity alignment and intercultural engagement. Community involvement was also found to impact perceived cultural exchange positively. The findings offer theoretical contributions by reconceptualizing place branding as a dialogic and identity-forming process and practical implications for designing culturally responsive branding strategies rooted in local narratives and community participation.